NILAI TAMBAH EKONOMI PENGOLAHAN JAMBU METE INDONESIA - Listyati, Dewi; Sudjarmoko, Bedy (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Economic value added of cashew processing in Indonesia. Cashew is one of the commodities that have significance for Indonesiaâs economy.Besides the country foreign exchange earner and source of income of farmers, cashew nuts contribute for land conservation. In Indonesia, cashew mostlycultivated by smallholders. The main problem is the low productivity of Indonesian cashew crop and quality of products. The development of thecashew processing industry faced with the constraint of continuity of availability of raw materials. This is because cashew harvest season is generallyonly four months (July-October) per year. Indonesia cashew exports still largely in the raw form, especially to India and Vietnam which is a majorproducer of cashew in the world market. The dominant raw form of cashew export is not benefeting farmers, processing industry and the government(central and local). The loss potential lost opportunity to obtain economic value added, the amount of Rp 1.8 to 2.9 trillion per year. Opportunitycomes from the processing of cashew nuts and CNSL. This product price is stabilize, the market outlook is still very open, both domestic andinternational markets. Demand for exports and growing domestic market, it should be an incentive for farmers, processing industry, and government toexploit its full potential. Besides the increase farmers income, this step will open new employment opportunities in rural as well as opportunitiesincrease foreign exchange. This potential will only materialize if the processing performed by the industry to involve farmers as partners.